Desenvolvimento de métodos analíticos para especiação de As(III) e As total e determinação de Cd, Cr e Pb em fertilizantes fosfatados utilizando espectrometria de absorção atômica e extração assistida por ultrassom - Rezende, Helen Cristine de (2014)
In this study, methodologies for determination of contaminant metals in phosphate fertilizers were developed. For determination of inorganic arsenic species was employed Atomic Absorption Spectrometry with Hydride Generation (HG AAS) and Cd, Cr and Pb were determinate by Atomic Absorption Spectrometry with Graphite Furnace (GF AAS). In the determination of inorganic arsenic the variables which affect the hydride generation step were optimized using univariate analysis. The determination of As(III) was performed through the simple control of solution pH with a 0.5 mol L-1 citric acid/sodium citrate buffer solution at pH 4.5 and total arsenic is determined after a pre-reduction reaction with 1.0% w/v thiourea. Cadmium, lead and chromium were determined by GF AAS and the temperature programs were optimized in order to achieve greater analytical efficiency and the study consisted of a screening of permanent modifiers, pyrolysis and atomization temperature. Ultrasound-assisted acid extraction was performed to prepare the samples and parameters sonication time, concentration and type of extractor were optimized using multivariate experiments. Limits of quantification were 0.097 mg Kg-1 for As (III), 0.074 mg Kg-1 for As Total and 0.11, 0.63 and 0.90 mg L-1 for Cd, Cr and Pb, respectively. Precision was expressed as RSD (%), and was less than 5 % and the accuracy of the method was evaluated by analysis of certified material NIST SRM 695, not significant difference at a level of 95 % with the certified values, were observed. The method was applied in the analysis of phosphate fertilizers produced in the Brazil and the levels found were below the maximum values established by brazilian legislation.